Characterization of Virus-Inducible Orchid Argonaute 5b Promoter and Its Functional Characterization in Nicotiana benthamiana during Virus Infection - Kasi Viswanath, Kotapati; Kuo, Song-Yi; Huang, Ying-Wen; Tsao, Nai-Wen; Hu, Chung-Chi; Lin, Na-Sheng; Wang, Sheng-Yang; Hsu, Yau-Heiu (International journal of molecular sciences, 2022)
Plant ARGONAUTES (AGOs) play a significant role in the defense against viral infection. Previously, we have demonstrated that AGO5s encoded in Phalaenopsis aphrodite subsp. formosana (PaAGO5s) took an indispensable part in defense against major viruses. To understand the underlying defense mechanism, we cloned PaAGO5s promoters (pPaAGO5s) and analyzed their activity in transgenic Nicotiana benthamiana using β-glucuronidase (GUS) as a reporter gene. GUS activity analyses revealed that during Cymbidium mosaic virus (CymMV) and Odontoglossum ringspot virus (ORSV) infections, pPaAGO5b activity was significantly increased compared to pPaAGO5a and pPaAGO5c. Analysis of pPaAGO5b 5′-deletion revealed that pPaAGO5b_941 has higher activity during virus infection. Further, yeast one-hybrid analysis showed that the transcription factor NbMYB30 physically interacted with pPaAGO5b_941 to enhance its activity. Overexpression and silencing of NbMYB30 resulted in up- and downregulation of GUS expression, respectively. Exogenous application and endogenous measurement of phytohormones have shown that methyl jasmonate and salicylic acid respond to viral infections. NbMYB30 overexpression and its closest related protein, PaMYB30, in P. aphrodite subsp. formosana reduced CymMV accumulation in P. aphrodite subsp. formosana. Based on these discoveries, this study uncovers the interaction between virus-responsive promoter and the corresponding transcription factor in plants.